Effects of Tai Chi combined with intermediate frequency therapy on patients with chronic nonspecific neck pain: a randomized controlled trial - Deng, Kangni; Zhou, Yuheng; Qian, Jiasi; Wang, Lilin; Yu, Fan; Wang, Bo (Frontiers in Pain Research, 2025)
BackgroundChronic non-specific neck pain (CNSNP) is the most common type of chronic neck pain encountered in clinical practice. Existing studies have demonstrated that intermediate frequency therapy can effectively alleviate neck pain symptoms. Among other conservative treatment modalities, Tai Chi, a typical mind-body exercise, may improve musculoskeletal function and postural control, but its effect on cervical stability and CNSNP remains unclear. The aim of this study was to compare the clinical efficacy of Tai Chi combined with intermediate frequency therapy vs. intermediate frequency therapy alone in patients with CNSNP.MethodsAccording to the inclusion and exclusion criteria, patients with CNSNP were recruited from the rehabilitation medicine clinic of the Sixth People's Hospital of Kunshan City, resulting in the enrollment of 60 eligible participants. Patients were randomly assigned to either the experimental group (EG) or the control group (CG). The EG received Tai Chi combined with intermediate frequency therapy, while the CG received intermediate frequency therapy alone. The primary outcome was the visual analogue scale (VAS) for pain. Secondary outcomes included the Neck Disability Index (NDI), the D value of cervical physiological curvature measured by x-ray, and the cervical range of motion (ROM) score. The intervention lasted eight weeks, with sessions conducted five times per week, for a total of 40 sessions. Assessments were performed at baseline, at four weeks (mid-intervention), and at the end of eight weeks.ResultsDuring the study, one participant in the EG withdrew after missing one week of Tai Chi intervention. Two participants in the CG discontinued: one due to a change in their treatment plan, and one for personal reasons. Thus, 57 patients with CNSNP completed the study. Both groups showed significant improvements in VAS, NDI, cervical physiological curvature (D value), and ROM scores after treatment compared to baseline. Notably, the improvement in the D value was significantly greater in the EG than in the CG.ConclusionFor patients with CNSNP, the combination of Tai Chi and intermediate frequency therapy appeared to alleviate pain and improve function. Compared to intermediate frequency therapy alone, this combined approach significantly improves the physiological curvature of the cervical spine in individuals with CNSNP. Furthermore, these findings suggest that Tai Chi may be a safe and beneficial adjunctive therapy, and may represent a promising alternative for the management of CNSNP. However, larger-scale long-term studies are still needed.Clinical Trial Registration:www. itmctr.ccebtcm.org.cn, identifier (TTM-CTR-2025000447).